1979
DOI: 10.1111/j.1399-6576.1979.tb01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Neurolept Anaesthesia in Patients with Coronary Artery Disease

Abstract: An anaesthetic technique comprising a combination of phenoperidine (0.1 mg . kg-1), diazepam (0.06 mg . kg-1) and pancuronium bromide (0.1 mg . kg-1) with controlled ventilation was evaluated in 12 patients with severe coronary artery disease. The heart rate, cardiac output and mean arterial blood pressure did not change significantly between the preinduction and postinduction measurements. The right atrial pressure and pulmonary capillary wedge pressure decreased significantly by 33% and 36%, respectively, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This beneficial effect has yet to be demonstrated in the presence of increased ventricular filling pressures in man. It would therefore seem logical to control hypertension during operation by the adoption of an anaesthetic technique which has a reputation for maintaining cardiovascular stability without depressing ventricular function (Tyden and Westerholm, 1979) by using moderate betablockade (by discontinuing beta-blocking agents 12-24h before surgery) and augmenting these with direct-acting vasodilators. Kaplan and Jones (1979) compared nitroprusside with nitroglycerine freshly prepared in the hospital pharmacy and showed that both drugs directly affect vascular smooth muscle and will decrease arterial pressure by a balanced dilation of resistance and capacitance vessels during anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect has yet to be demonstrated in the presence of increased ventricular filling pressures in man. It would therefore seem logical to control hypertension during operation by the adoption of an anaesthetic technique which has a reputation for maintaining cardiovascular stability without depressing ventricular function (Tyden and Westerholm, 1979) by using moderate betablockade (by discontinuing beta-blocking agents 12-24h before surgery) and augmenting these with direct-acting vasodilators. Kaplan and Jones (1979) compared nitroprusside with nitroglycerine freshly prepared in the hospital pharmacy and showed that both drugs directly affect vascular smooth muscle and will decrease arterial pressure by a balanced dilation of resistance and capacitance vessels during anaesthesia.…”
Section: Discussionmentioning
confidence: 99%